MEKANISME PENYELESAIAN PEMBAYARAN KEGIATAN EKSPOR IMPOR DENGAN MENGGUNAKAN LETTER OF CREDIT DAN BILL EXCHANGE - Suyanti Suyanti (Majalah Ilmiah Bahari Jogja, 2016)
In the last few years, international trading undergoes rapid-like program so that purchasing import increases significantly. As one of the example of it is that buyers can order product from certain country via bank. This kind of activities is under custom regulation on commercial affairs. On the other hand, documentary credit is effectively used since 1983. Some of important documents should be available or included during the transaction. Since the bank requires these documents, payment is assumed to be noted if only buyers succeed in providing the documents.